North American Free Trade Agreement : its impact on Caribbean Basin economies. - Lewis, David E. (1991)
Highlights some aspects of the Enterprise of the Americas Initiative, viz, investment, debt and trade, of which trade has become the most strategic aspect. Points out that the reduction of trade barriers under an FTA would partly displace US trade with other countries, and the relative benefits of tariff preference schemes, such as the GSP and the CBI, to these third countries are likely to decrease.